Antenatal influenza vaccination in urban Pune, India: clinician and community stakeholders' awareness, priorities, and practices. Issue 4 (3rd April 2021) - Giduthuri, Joseph G.; Purohit, Vidula; Kudale, Abhay; Utzinger, Jürg; Schindler, Christian; Weiss, Mitchell G.
ABSTRACT: The World Health Organization (WHO) recommends antenatal influenza vaccination (AIV) for pregnant women at any stage of pregnancy. This study assessed fundamental aspects of AIV acceptance and demand among key stakeholders in urban Pune, India. Semi-structured interviews for rapid ethnographic assessment of AIV-related awareness, priorities, and practices were used to study clinicians and their communities of practice. A qualitative survey was conducted among 16 private clinicians providing antenatal care (ANC) in slum and middle-class areas of Pune. Following the survey, clinicians were informed about authoritative AIV recommendations. A qualitative community survey was also conducted with 60 women aged 20–35 years and 30 spouses from the same slum and middle-class practice areas of the ANC providers. Subsequently, a second clinician survey was conducted to assess changes in clinicians' awareness, priority, and vaccination practice. After this interview, clinicians were informed of community survey findings. Most community respondents were unaware of AIV, in contrast with well-known and widely used antenatal tetanus vaccination. They expressed confidence in vaccines and trust in the clinicians. Clinicians' advice was reportedly the most important determinant of community vaccine acceptance. Clinicians were confident of the safety of AIV and they anticipated patients' acceptance if recommended. The second clinician interview showed increased awareness of AIV policy, but clinicians were more skeptical about the severity of maternal influenza in their practice. Our findings indicate community acceptance though not demand for AIV. We recommend five essential elements for vaccination program strategies to improve coverage with AIV and other ANC vaccines.